Laparoscopic versus Open Colectomy for Elderly Patients with Colon Cancer: A Propensity Score Analysis with the Controlling Nutritional Status (CONUT) Score. (7th February 2021) - Horie, Tomoko; Shida, Dai; Ahiko, Yuka; Takamizawa, Yasuyuki; Inoue, Manabu; Tanabe, Taro; Nakamura, Yuya; Imaizumi, Jun; Tsukamoto, Shunsuke; Kanemitsu, Yukihide
Abstract: The feasibility of laparoscopic surgery for elderly patients remains unclear, as these patients usually present with comorbidities. Recently, the controlling nutritional status (CONUT) score has drawn attention as an evaluation score of patients' general status as well as a predictor of survival. We retrospectively analyzed overall survival in 424 patients aged ≥75 years with colon cancer, who underwent curative surgery (laparoscopic ( n = 167) or open surgery ( n = 257)) between January 2004 and December 2013. To adjust for heterogeneity in both groups, a propensity score-matched analysis was performed, with the CONUT score as a confounding covariate. 5-year overall survival rates of patients with normal (0–1), mildly abnormal (2–4), or abnormal (≥5) CONUT score were 88.6%, 79.4%, and 41.4%, respectively ( p < 0.001). T3 or less, N negative, late period (2009–2013), and normal CONUT score were associated with the tendency to undergo laparoscopic surgery ( p < 0.001). The analysis of the propensity score-matched cohort (124 pairs) revealed that patients in the laparoscopic surgery group had a similar prognosis to those in the open surgery group, with a 5-year overall survival of 91.9% vs. 82.0%, respectively ( p = 0.102). Laparoscopic surgery for colon cancer is an acceptable surgical approach in elderly patients.